Characterization of antimicrobial compounds from Combretum paniculatum, a plant with proven anti-HIV replication activity - Eloff, Jacobus Nicolaas (University of Pretoria, 2013)
Thesis (PhD (Paraclinical Science))--University of Pretoria, 2007.